Correlation between maxillary central incisor form and face form in 4 racial groups - Varjao, Fabiana Mansur; Nogueira, Sergio Sualdini [UNESP]; Russi, Sergio; Arioli Filho, João Neudenir [UNESP] (Quintessence Publishing Co Inc, 2006)
Objectives: the purpose of this study was to evaluate the correlation between central incisor form and face form in 4 racial groups and to investigate if there was agreement among experts in categorizing the central incisor forms. Method and Materials: A total of 160 subjects (40 whites, 40 mulattos, 40 blacks, and 40 Asians) ranging from 18 to 33 years of age were selected. Digital photographic records were made, 1 full-face and 1 intraoral view of the maxillary right central incisor. The outline tracings of the tooth and face images were obtained using Adobe Photoshop 5.0 software. The outline tracings were printed in distinct transparencies, and 3 prosthodontists determined if there was correspondence between the tooth and the face forms by superimposition of the transparencies. If there was disagreement among the prosthodontists' evaluations, the prevalent decision was considered. The experts also classified the central incisor forms into square, ovoid, tapering, or combination at 2 different sessions. At the first session, no instructions were given. At the second session, the prosthodontists were instructed to follow Williams' method of classification. Results: A correspondence between tooth and face forms was found in 23.75% of all cases. Agreement on the tooth form classifications among the prosthodontists occurred in 30.62% of all cases at the first session and 24.37% at the second session. Conclusion: There is not a highly defined correlation between central incisor form and face form in any racial group studied. In addition, the experts were not in fair agreement in categorizing tooth forms.
Keywords: artificial teeth; complete denture; esthetics; facial morphology; race; tooth morphology